Impacts of land use and cropland management on soil organic matter and greenhouse gas emissions in the Brazilian Cerrado. (9th November 2020) - Siqueira‐Neto, Marcos; Popin, Gustavo Vicentini; Piccolo, Marisa C.; Corbeels, Marc; Scopel, Eric; Camargo, Plínio B.; Bernoux, Martial
Abstract: The Brazilian Cerrado is a large and expanding agricultural frontier, representing a hotspot of land‐use change (LUC) from natural vegetation to farmland. It is known that this type of LUC impacts soil organic matter (SOM) dynamics, particularly labile carbon (C) pools (living and non‐living), decreasing soil health and agricultural sustainability, as well as increasing soil greenhouse gas (GHG) emissions, and accelerating global climate change. In this study, we quantified the changes in the quantity and quality of SOM and GHG fluxes due to changes in land use and cropland management in the Brazilian Cerrado. The land uses studied were native vegetation (NV), pasture (PA) and four croplands, including the following management types: conventional tillage with a single soybean crop (CT), and three no‐tillage systems with two crops cultivated in the same year (i.e., soybean/sorghum (NTSSo ), soybean/millet (NTSMi ) and maize/sorghum (NTMSo )). Soil and gases were sampled in the rainy season (November, December and January) and dry season (May, July and September). The highest soil C and nitrogen (N) stocks (6.7 kg C m −2 and 0.5 kg N m −2, 0–0.3‐m layer) were found under NV. LUC reduced C stocks by 25% in the CT and by 10% in the PA and NT. Soil N stocks were 30% lower in the PA and NTMSo and 15% lower in the croplands with soybean compared to NV. δ 13 C values clearly distinguished between the C‐origin from NV (−25‰) and that from other land uses (−16‰). Soil (0–0.1 m) under NV also presented higher labile‐C (625 g C m −2 ), microbial‐C (70 g C m −2 ) and microbial‐N (5.5 g N m −2 ), whereas other land uses presented values three times lower. GHG emissions (expressed as C‐equivalent) were highest in the NV (1.2 kg m −2 year −1 ), PA (1.3 kg m −2 year −1 ) and NTMSo (0.9 kg m −2 year −1 ) and were positively related to the higher SOM turnover in these systems. Our results suggest that in order to maintain SOM, it is necessary to adopt "best" management practices, that provide large plant residue inputs (above‐ and belowground). This can be seen as a pathway to achieving high food production with low GHG emissions.